Resilience in Post-Truth and Post-Digital European Union: Youth-Led Civil Society Organisations in the 2024 European Elections - Pane, Sara (PARTECIPAZIONE E CONFLITTO, 2026)
In an era marked by epistemic instability, algorithmic disruption and institutional disaffection, the European Union faces a deepening crisis of communicative legitimacy. This article investigates the role of youth-led civil society organizations (CSOs) as agents of communicative resilience within the evolving landscape of European public institutional communication, focusing on the 2024 European Parliament elections. Drawing on 35 qualitative interviews with CSO representatives involved in the Use Your Vote institutional communication campaign, the study examines how these actors operate simultaneously as actors of disintermediation and multipliers of EU messaging. Through localized, participatory and pedagogical practices, youth-led CSOs rearticulate abstract institutional narratives into context-sensitive forms of civic engagement, countering information disorder and reconnecting citizens—especially in peripheral territories—with the European project. The research highlights how these organizations combine digital tools with offline presence and non-formal education to foster trust, critical awareness and democratic participation. It further explores emerging tensions surrounding the use of generative AI in civic communication, calling for a reflexive and situated approach to digital innovation. Ultimately, the article contends that strengthening communicative resilience in the post-truth and post-digital public sphere requires institutional recognition of civil society’s constitutive role in shaping democratic discourse.